The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.15761/ahdvs.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Serum, milk, saliva and urine progesterone and estradiol profiles in crossbred (Zebu x Holstein Friesian) dairy cattle

Abstract: Effective breeding management is a crucial tool to enhance the reproductive and productive performance of dairy cattle. To achieve this, regular monitoring of their reproductive status is important. The aims of this study were to monitor the reproductive status of crossbred dairy cattle based on progesterone (P4) concentration in serum, whole milk, saliva and urine, and estradiol in serum using quantitative laboratory ELISA tests, and to document hormonal profiles at different reproductive stages. Three hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Similarly, El-Fouly et al (1998a) showed that E2-17β levels in crossbred cows did not change in the 1 st trimester while it significantly increased in the 2 nd trimester and increased sharply at the end of the 3 rd trimester of gestation, reached to its peak on day 1 before calving. Mekonnin et al (2017) conducted a study for estradiol level detection in pregnant heifers and cows. In both cows and heifers, higher estradiol concentrations were recorded during the first trimester of pregnancy as compare to other stages of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, El-Fouly et al (1998a) showed that E2-17β levels in crossbred cows did not change in the 1 st trimester while it significantly increased in the 2 nd trimester and increased sharply at the end of the 3 rd trimester of gestation, reached to its peak on day 1 before calving. Mekonnin et al (2017) conducted a study for estradiol level detection in pregnant heifers and cows. In both cows and heifers, higher estradiol concentrations were recorded during the first trimester of pregnancy as compare to other stages of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Progesterone has a substantial role in the reproductive health, such as regulating the estrous cycle time-length, maintaining pregnancy (Ab et al, 2017). In veterinary medicine, progesterone measurements have helped to improve fertility, used to assess the reproductive status of the cow and to diagnose pregnancy (Blavy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many of studies have investigated different methods to monitor PG in cows in different media such as milk (Samsonova et al, 2018) (Blavy et al, 2016),blood (Lasheen et al, 2018), urine (Volkery et al, 2012), and saliva (Ab et al, 2017) . The efficacy of biotechnologies for synchronization of estrus in cattle is fundamentally dependent on the PG quantitation in biologic fluids.…”
Section: Introductionmentioning
confidence: 99%